Exploring how design guidelines benefit design engineers: an international and global perspective. (2020) - Reimlinger, Benedikt; Lohmeyer, Quentin; Moryson, Ralf; Meboldt, Mirko
Abstract : A multitude of design guidelines that are intended to support design engineers with knowledge and information during the embodiment design of physical products have been developed back in the 1980s and 1990s. However, since then, the setting in which products are developed and designed has changed and associated tasks and activities are carried out globally rather than locally. Yet, knowledge on the benefit of such design guidelines and their impact on the performance of multinational design engineers from different regions and with different levels of experience is still lacking. To address this, a mobile eye tracking study has been developed and carried out with 47 differently experienced practitioners from Germany, Eastern Europe and Asia. The results show differences in how design engineers from different regions with different levels of experience may benefit from design guidelines and how design guidelines may impact experts' and novices' performance, indicate beneficial ways of using them and point out the kind of information and the way of representation that attracts the most attention within a design guideline. The paper concludes that the improvement and development of design guidelines that are intended to support the embodiment design of physical products is needed and proposes to rethink current engineering design guidelines both content-wise and representation-wise.